Analisis Fundamental Kinerja Keuangan Terhadap Pertumbuhan Perusahaan Terdaftar di BEI - Muliyani, Muliyani; Putri, Viona Saskia; Tanjung, Ahmad Albar (Graha Mitra Edukasi, 2024)
This research aims to conduct a fundamental analysis of PT Summarecon Agung Tbk, a leading property development company in Indonesia. Fundamental analysis is one of the measurement methods used by investors to determine the safety of a stock value. This method is carried out by examining the financial factors and economic conditions of related companies. In this study, secondary data in the form of financial statements of PT Summarecon Agung Tbk were analysed to assess financial ratios such as liquidity, activity, solvency, profitability and market ratios. In addition, external factors such as macroeconomic conditions, interest rates, inflation, and property industry trends in Indonesia were also considered. Observations were made of financial reports published on the Indonesia Stock Exchange (IDX) website for the period 2019-2023. The analysis results show that the financial performance of PT Summarecon Agung Tbk is in good and stable condition. Financial performance based on the liquidity ratio shows a value greater than 1, so it can be concluded that the liquidity of SMRA is in good condition and SMRA is able to pay off existing current liabilities. The solvency ratio shows a value greater than one, which indicates that the capital structure of SMRA is dominated by equity rather than debt. Based on the activity, profitability and EPS ratios, it is found that the lowest performance occurred in 2020 due to the Covid-19 pandemic.